Mussolini 1883-1915 Triumph and Transformation of a Revolutionary Socialist - Di Scala, Spencer M.; Gentile, Emilio; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This book describes Mussolini's little-known radical ideology, including his activities in Switzerland, relationship with revolutionary syndicalism, and radical journalism. It provides an in-depth treatment of the young Benito Mussolini as a revolutionary Socialist and describes the political maneuverings that took a major European Socialist party by storm before the First World War. It explains the process of how he came to dominate Italian Socialism until the crisis caused by Italy's intervention in World War I. It illuminates Mussolini's leadership qualities and his rise to leader of the Italian Socialist Party.
Keywords: Italy-History.; World politics; Military History; History, Modern